Proteoma salivar em pacientes com cancro da cabeça e do pescoço - Maltez, Elsa (2015)
After irreversible mutations in a cell, this can enter in a tumourogenese state evolving from a normal state to a hyperplasic originating a carcinoma in situ followed by an invasive carcinoma. There is also different aetiologic agents like tobacco, alcohol, a deficient diet and oral hygiene or viral infections that will promote the occurrence of mutations and the development of a possible invasive carcinoma. Head and neck cancers represent 5% of all cancers in Portugal with a mortality rate of about 50%, being a huge problem in public health. This way it becomes important to discover a new diagnosis method to discover and identify head and neck cancers as soon as possible to provide an effective treatment. Saliva, composed by proteins have been recently investigated and proved to be a very useful sample in the detection of different types of diseases when associated with Molecular Biology techniques. Recent proteomic and peptidomic analysis showed that increased expression levels of proteins or proteases in saliva could indicate diferent health status. This work addresses the first exploratory study regarding salivary proteases and peptidome with head and neck cancer patients. Results lead us to think in each way animal viruses are implicated in some human cancers and if they're latency state help in the development of cancer. Proteolytic analysis revealed that maybe it would be possible to detect larynx and oropharynx cancers in previous stages but we need further studies to comprise that.